Understanding the effects of salinity and Vibrio harveyi on the gut microbiota profiles of Litopenaeus vannamei - Deris, Zulaikha Mat; Iehata, Shumpei; Gan, Han Ming; Ikhwanuddin, Mhd; Najiah, Musa; Asaduzzaman, Md; Wang, Min; Liang, Yantao; Danish-Daniel, Muhd; Sung, Yeong Yik; Wong, Li Lian (Frontiers in Marine Science, 2022)
Increasing shreds of evidence have revealed a positive correlation between gut microbiota and shrimp health, in which a healthy shrimp gut is consisted of a complex and stable microbial community. Given that both abiotic and biotic factors constantly regulate shrimp gut microbiota, the climatic changes affecting the levels of these factors could cause disease outbreaks. The goal of this study was to explore the effects of salinity levels and pathogenic Vibrio harveyi infection on the diversity, structure, composition, interspecies interaction, and functional pathways of Penaeus vannamei gut microbiota. Juvenile shrimp were cultured at 5 ppt, 20 ppt, and 30 ppt (control condition) for two months prior to Vibrio harveyi infection. After the 24-hour challenge test, genomic DNA was isolated from the shrimp gut, and subjected to the 16S rRNA metagenomic sequencing analysis. We observed that gut microbiota diversity of shrimp cultured at 5 ppt and 30 ppt were lower than 20 ppt after exposure to V. harveyi infection, suggesting that shrimp cultured at the two former salinity levels were more susceptible to disease infection. Network analysis also showed that shrimp cultured at 20 ppt exhibit a more stable bacterial network with complex interspecies interaction, even after induced by V. harveyi. Moreover, the presence of a high number of beneficial bacteria such as Pseudoruegeria, Rhodovulum, Ruegeria, Shimia and Lactobacillus in shrimp cultured at 20 ppt might have played a role in inhibiting the growth of V. harveyi and other potentially pathogenic bacteria. Bacterial functional pathway prediction has also detected a significantly higher biofilm formation process in the gut microbiota of shrimp cultured at 20 ppt, following V. harveyi infection. Collectively, our results suggested that 20 ppt is an optimal salinity that suppresses the growth of V. harveyi and potentially pathogenic bacteria in the shrimp gut, which could possibly minimize the risk of disease infection in shrimp for healthy shrimp production.